Effect of laser irradiance on the surface morphology and laser induced plasma parameters of zinc. (March 2014) - Akram, Mahreen; Bashir, Shazia; Hayat, Asma; Mahmood, Khaliq; Ahmad, Riaz; Khaleeq-U-Rahaman, M.
Abstract: The effect of laser-irradiance on the surface morphology and laser induced breakdown spectroscopy of zinc has been investigated by employing Nd:YAG laser (wavelength λ = 1064 nm, pulse duration t 10 ns, and repetition rate = 10 Hz) under ambient environment of argon at a pressure of 20 Torr. For this purpose, zinc targets were exposed to various laser irradiances ranging from 13 GW/cm 2 to 100 GW/cm 2 . Scanning electron microscope analysis has been performed to analyze the surface modification of irradiated zinc targets. Scanning electron microscope analysis revealed the formation of various kinds of structures such as ripples, cones, cavities, and wave like ridges at the center and peripheral regions of ablated zinc. In the central ablated region with increasing laser irradiance, the growth of distinct and well defined ripples is observed. Further increase in irradiance makes the appearance of these ripples diffusive and narrow. In order to correlate the plasma parameters with the surface modification, laser induced breakdown spectroscopy analysis has also been performed. The electron temperature and number density of zinc plasma have been evaluated at various laser irradiances. For both plasma parameters, an increasing trend up to a certain value of laser irradiance is observed which is due to enhanced energy deposition. Afterword a decreasing trend is achieved which is attributed to the shielding effect. With further increase in irradiance a saturation stage comes and almost no change in plasma parameters is observed. This saturation is explainable on the basis of the formation of a self-regulating regime near the target surface. A strong correlation between surface modification and plasma parameters is established.